PENGARUH ARUS KAS OPERASI, UMUR PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2016 - Aprilia Louise Cardilla; Mochamad Muslih; Dedi Rianto Rahadi (FIRM Journal of Management Studies, 2019)
Among the 3 (three) cash flows contained in a company, the cash flows from operations are considered to be the most important cash flow in the company and most determine the success of the company in achieving its main objective, namely profit optimally. The purpose of this study was to study the effect of cash flows from operating activities, company size, and company age on company profits. The research method used is the quantitative research method, using the ordinary least square method. The unit of analysis is the company. Sample selection is done purposively. The sample is 12 banking companies listed on the Bursa Effek Indonesia.The results showed that cash flows from operating activities and company size did not have a significant effect on corporate profits. The age variable of the company turned out to have a significant effect on company profits, but the sign or the coefficient was reversed. This means that the older the company age, the lower the company's profit.